Aromaticity and degree of aromatic condensation of char. (January 2015) - Wiedemeier, Daniel B.; Abiven, Samuel; Hockaday, William C.; Keiluweit, Marco; Kleber, Markus; Masiello, Caroline A.; McBeath, Anna V.; Nico, Peter S.; Pyle, Lacey A.; Schneider, Maximilian P.W.; Smernik, Ronald J.; Wiesenberg, Guido L.B.; et al.
Graphical abstract: Highlights: Measurements from 38 laboratory chars using 7 characterization methods were compared. Most measurements captured the aromaticity or aromatic condensation degree. Aromaticity and condensation degree showed distinct patterns with charring temperature. Simple methods potentially capture char aromatic features as well as more costly ones. Abstract: The aromatic carbon structure is a defining property of chars and is often expressed with the help of two concepts: (i) aromaticity and (ii) degree of aromatic condensation. The varying extent of these two features is assumed to largely determine the relatively high persistence of charred material in the environment and is thus of interest for, e.g., biochar characterization or carbon cycle studies. Consequently, a variety of methods has been used to assess the aromatic structure of chars, which has led to interesting insights but has complicated the comparison of data acquired with different methods. We therefore used a suite of seven methods (elemental analysis, MIR spectroscopy, NEXAFS spectroscopy, 13 C NMR spectroscopy, BPCA analysis, lipid analysis and helium pycnometry) and compared 13 measurements from them using a diverse sample set of 38 laboratory chars. Our results demonstrate that most of the measurements could be categorized either into those which assess aromaticity or those which assess the degree of aromatic condensation. A variety of measurements, including relatively inexpensive and simple ones, reproducibly captured the two aromatic features in question, and data from different methods could therefore be compared. Moreover, general patterns between the two aromatic features and the pyrolysis conditions were revealed, supporting reconstruction of the highest heat treatment temperature (HTT) of char.